Soil Characteristics under Introduced Cryptomeria japonica (Dhupi) in Darjeeling Himalayan Region - Singh, Balvinder; Nath, S.; Das, P. K.; Singh, S. B.; Banerjee, S. K. (Indian Forester, 1987)
The nature and properties of the soils supporting Cryptomeria japonica in Darjeelling Himalayan Region were studied. The soils are acidic and contain high organic matter. The growth parameters are inversely related to the pH and organic matter of the soils while height of plants and basal area of tbe species are positively correlated with C.E.C., exch. Ca+2,Mg+2, K+ and available phosphorus. Total nitrogen contents of the soils are correlated positively with G.B.H. and basal area but negatively with the heights of the plants. Ranges of some of the attributes suitable for the growth of the species under more or less similar climatic conditions are assessed.